Rice husk ash as a substitute for silica gel - Rahmad Bonanza; Dan Mugisidi (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Silica gel has been widely used as a dryer for food, medicine and various other purposes. Silica gel is basically a safe material, but because of its hydroscopic nature, silica gel is easily contaminated with dangerous materials. Apart from that, silica gel cannot decompose easily naturally, so using large amounts of silica gel will cause piles of silica gel waste. Therefore, efforts are being made to find replacement materials, one of which is using rice husk ash which can easily decompose naturally. This research aims to test the ability of rice husk ash as a substitute for silica gel. Tests used commercial silica gel (SG), silicon gel in non-woven geotextile bags (SG-N), and rice husk ash in non-woven geotextile bags (AS-N). In this study, AS-N was compared with SG and SG-N. The water vapor absorption test was carried out on a weight of 15 grams for 180 minutes. Each of the three samples was placed in a closed jar to avoid contamination with water vapor in the environment. The relative humidity of each jar was measured with a hygrometer. The jar lid was kept closed throughout the test. The results showed that SG, SG-N and AS-N reduced humidity by 23%, 22% and 24% respectively. Modeling with the Avrami equation is used to extrapolate the absorption results. The research results showed that 15 gram non-woven geotextile rice husk ash had superior water vapor absorption capabilities compared to silica gel and silica gel non-woven geotextiles. So it can be concluded that dryers with rice husk ash as the basic material can be used for needs such as clothes dryers, food dryers and other needs